2019
DOI: 10.1186/s12938-019-0634-5
|View full text |Cite
|
Sign up to set email alerts
|

A pap-smear analysis tool (PAT) for detection of cervical cancer from pap-smear images

Abstract: BackgroundCervical cancer is preventable if effective screening measures are in place. Pap-smear is the commonest technique used for early screening and diagnosis of cervical cancer. However, the manual analysis of the pap-smears is error prone due to human mistake, moreover, the process is tedious and time-consuming. Hence, it is beneficial to develop a computer-assisted diagnosis tool to make the pap-smear test more accurate and reliable. This paper describes the development of a tool for automated diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 50 publications
0
49
0
1
Order By: Relevance
“…Notably, however, none of the slides that were classified as negative by the DLS were classified as atypical in the cytodiagnosis of the physical slides. Previous studies have reported encouraging results with the deep learning–based analysis of smaller cropped images from Papanicolaou smears 26 , 27 , 29 , 39 that were digitized with conventional slide scanners, but clinical application requires the examination of substantially larger sample areas. 28 In this study, we used routine samples collected at the clinic, and correspondingly, the whole-slide images were magnitudes larger than those previously analyzed, measuring on average 100 387 × 47 560 pixels; thus, the total number of pixels analyzed corresponded to approximately twice the number in the entire ImageNet database (>14 million images of everyday objects) at commonly used resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, none of the slides that were classified as negative by the DLS were classified as atypical in the cytodiagnosis of the physical slides. Previous studies have reported encouraging results with the deep learning–based analysis of smaller cropped images from Papanicolaou smears 26 , 27 , 29 , 39 that were digitized with conventional slide scanners, but clinical application requires the examination of substantially larger sample areas. 28 In this study, we used routine samples collected at the clinic, and correspondingly, the whole-slide images were magnitudes larger than those previously analyzed, measuring on average 100 387 × 47 560 pixels; thus, the total number of pixels analyzed corresponded to approximately twice the number in the entire ImageNet database (>14 million images of everyday objects) at commonly used resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly because TCT images are relatively difficult to analyze compared to the pap smear images. More specifically: (1) the TCT images do not currently have a good database, and the collection of such an image database is more difficult compared to the Harlve database of pap-smear images [ 38 , 39 ]; (2) TCT images have many overlapping cells, which are not as easy to analyze as the single cells in pap-smear images [ 40 , 41 ]; (3) the color and quality of TCT images obtained from different medical institutions may vary greatly. Therefore, these systems are poorly adapted for the proposed system, we trained it with data from hospitals at different levels in different regions of north and south China, which ensured the high adaptability of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported encouraging results with the deep learning-based analysis of smaller cropped images from Pap smears 26,27,29,39 that were digitized with conventional slide scanners, but clinical application requires the examination of substantially larger sample areas. 28 In this study, we used routine samples collected in the clinic, and correspondingly, the whole-slide images were magnitudes larger than those previously analysed, measuring on average 100,387 × 47,560 pixels; thus, the total number of pixels analysed corresponded to approximately twice the number in the entire ImageNet database at commonly used resolutions.…”
Section: Discussionmentioning
confidence: 99%